A Method to Measure The Resilience of Algorithm for Operation Management. Issue 12 (2016) - Han, B.; Liu, C.L.; Zhang, W.J.
Abstract: This paper proposes a new concept called resilience of algorithm in the context of operation management of a system. Resilience is a behavioral property of the system and it refers to the persistence of the system performance when the system is subject to damages. Operation management of a system can be modeled as a mathematical problem. Algorithms are to generate a solution to the mathematical problem. When a system is subject to damage, the corresponding mathematical problem is changed. The resilience of a system thus reduces to the issue of how and whether the existing algorithm can still generate a solution to the changed problem. This paper further proposes a measure of the resilience of algorithm and takes a supply chain scheduling algorithm as an example to validate the proposed measure. A simulated experiment is provided.